PENGARUH PEMBERDAYAAN SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI PADA KANTOR BKKBN PERWAKILAN PROVINSI SULAWESI SELATAN - Andi Firdania (FEB Universitas Lakidende, 2020)
The purpose of this research is to find out how to know the effect of human resource empowerment on the performance of BKKBN Office Employees representative of South Sulawesi Province. The population of this study is BKKBN office employee representative of South Sulawesi Province, sample numbering 37. This research is explanatory research, intending to explain the causal relationship between research variables and test pre-formulated hypotheses. Data retrieval instruments use documentation, questionnaires, and direct observations that are then analyzed using simple linear correlations. The result of the study obtained is that the implementation of empowerment assessment in employees has excellent criteria. While the performance of employees is also with very good criteria.